Edukasi Kesehatan Mental Remaja dan Dampaknya terhadap Pemahaman Tanda, Penyebab, dan Pencegahan Gangguan Psikologis - Abul A’la Al Maududi; Rafa Zemy Amalia; Nayla Jasmine Fadillah; Syaharani Laila Chaerunnisa Tengku; Siti Neza Azmarina; Siti Rosdiana; Riza Elhanina Ramadhani; Rizki Hashym (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Adolescent mental health is an essential component of optimal growth and development, yet it often receives less attention compared to academic achievement. Adolescents are in a vulnerable developmental stage characterized by emotional changes, social pressure, and environmental demands, which increase the risk of mental health problems. This activity aimed to improve knowledge and promote positive attitudes among junior high school students regarding adolescent mental health, including its definition, signs and symptoms, risk factors, and prevention strategies. The method used was a health education intervention employing a pre-test and post-test design. The activity was conducted at Al Amanah Junior High School, South Tangerang City, involving 25 students. The evaluation instrument consisted of a 10-item multiple-choice questionnaire with a maximum score of 100. The results showed that the average pre-test score was 98.40%, while the post-test score increased to 99.60%, indicating a 1.20% improvement. Although the increase was relatively small due to the high baseline knowledge (ceiling effect), the findings demonstrate that the educational intervention effectively reinforced students’ understanding of adolescent mental health. In addition, interactive discussions during the session contributed to increased awareness and reduced stigma related to mental health issues. This mental health education program has the potential to support early prevention efforts and foster a more supportive school environment for adolescents’ psychological well-being.